Four Fourier transform spectrometers and the Arctic polar vortex: instrument intercomparison and ACE-FTS validation at Eureka during the IPY springs of 2007 and 2008 - Batchelor, Rebecca L. (author); Kolonjari, F. (author); Lindenmaier, R. (author); Mittermeier, R. L. (author); Daffer, W. (author); Fast, H. (author); Manney, G. (author); Strong, K. (author); Walker, K. A. (author) (Atmospheric Measurement Techniques, 2010)
The Canadian Arctic Atmospheric Chemistry Experiment Validation Campaigns have been carried out at Eureka, Nunavut (80.05° N, 86.42° W) during the polar sunrise period since 2004. During the International Polar Year (IPY) springs of 2007 and 2008, three ground-based Fourier transform infrared (FTIR) spectrometers were operated simultaneously. This paper presents a comparison of trace gas measurements of stratospherically important species involved in ozone depletion, namely O3, HCl, ClONO2, HNO3 and HF, recorded with these three spectrometers. Total column densities of the gases measured with the new Canadian Network for the Detection of Atmospheric Change (CANDAC) Bruker 125HR are shown to agree to within 3.5% with the existing Environment Canada Bomem DA8 measurements. After smoothing both of these sets of measurements to account for the lower spectral resolution of the University of Waterloo Portable Atmospheric Research Interferometric Spectrometer for the Infrared (PARIS-IR), the measurements were likewise shown to agree with PARIS-IR to within 7%. Concurrent measurements of these gases were also made with the satellite-based Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) during overpasses of Eureka during these time periods. While one of the mandates of the ACE satellite mission is to study ozone depletion in the polar spring, previous validation exercises have identified the highly variable polar vortex conditions of the spring period to be a challenge for validation efforts. In this work, comparisons between the CANDAC Bruker 125HR and ACE-FTS have been used to develop strict criteria that allow the ground- and satellite-based instruments to be confidently compared. When these criteria are taken into consideration, the observed biases between the ACE-FTS and ground-based FTIR spectrometer are not persistent for both years and are generally insignificant, though small positive biases of ~5%, comparable in magnitude to those seen in previous validation exercises, are observed for ...